Evidence for Widespread Remagnetizations in South America, Case Study of the Itararé Group Rocks From the State of São Paulo, Brazil - Bilardello, Dario; Callebert, William C.; Davis, Joshua R. (Frontiers in Earth Science, 2018)
Paleomagnetism of South American Jurassic/ Cretaceous rocks has been troubled by elongated distributions of poles which has led to contrasting interpretations. Moreover, many discordant paleomagnetic poles from the Carboniferous to the Triassic have also been recognized and systematically explained by a variety of processes, but this portion of the South American apparent polar wonder path (APWP) still remains problematic. To this end, we have conducted a paleomagnetic study of the sedimentary Permo-Carboniferous Itararé Group rocks and three intruding mafic sills of likely Cretaceous age within the state of São Paulo, Brazil. The site-mean VGP distributions obtained from the sedimentary rocks define elongations that include the VGPs of the mafic intrusions. We interpret these distributions as remagnetization paths towards the directions characteristic of the sills. Furthermore, we show that the remanence directions of the sills are partially overprinted by the present time-averaged and current Earth's magnetic field. Our interpretations are supported by extensive rock-magnetic data that provides a viable mechanism for the secondary magnetizations. The current study focuses on the paleomagnetism and rock-magnetism of the mafic intrusions and how they affected the paleomagnetic recording of the sedimentary rocks, however, careful analysis of the paleomagnetic data of the Itararé sedimentary rocks enables isolation of a primary VGP distribution that is consistent with the reference Carboniferous pole position. Extending our study to other Carboniferous to Triassic South American paleomagnetic records reveals that the majority of these data are elongated, similarly to the Itararé Group rocks. Regardless of the age of the rocks, the elongations systematically intersect at the location of the Late Cretaceous reference pole, and at a long- recognized "problematic" location observed in some Jurassic and Cretaceous rock formations. Based on multiple lines of evidence, we interpret the elongations to reflect remagnetizations from the primary VGP positions towards Jurassic-Cretaceous pole locations that occurred as a result of the widespread magmatic events associated with the opening of the South Atlantic. We suggest that the extent of the remagnetizations is formation-specific, and that other rock-formations should be carefully re-evaluated.